The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1046/j.1540-8167.2004.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Electrical Remodeling After Cardioversion of Persistent Atrial Fibrillation

Abstract: The atrial effective refractory period increases, sinus node function improves, and atrial conduction velocity goes up in the first week after cardioversion of long-standing atrial fibrillation in humans. Reverse electrical remodeling of the effective refractory period occurs at different rates in different regions of the atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 28 publications
2
50
0
1
Order By: Relevance
“…The evidence in support of this conclusion is based on changes in atrial APD, ERP, CV, and P wave duration when measured 1–4 weeks after achieving sinus rhythm. 617,618,619,620 The changes in P wave duration occur more slowly and do not predict long-term maintenance of sinus rhythm. 619 An important question is whether AAD therapy can be used to prevent or initiate reverse remodeling even prior to ablation, thereby improving the success rate for ablation procedures.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence in support of this conclusion is based on changes in atrial APD, ERP, CV, and P wave duration when measured 1–4 weeks after achieving sinus rhythm. 617,618,619,620 The changes in P wave duration occur more slowly and do not predict long-term maintenance of sinus rhythm. 619 An important question is whether AAD therapy can be used to prevent or initiate reverse remodeling even prior to ablation, thereby improving the success rate for ablation procedures.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…One study reported that the recurrence rate of AF following ablation was lower when treatment with dofetilide prior to ablation reduced the burden of AF, and was associated with a decrease in P wave duration. 617,618 Another single-center nonrandomized study found that amiodarone prolonged the cycle length of AF and reduced the time spent on CFAE ablation, but it did not have any effect on long-term outcomes. 619 A second single-center study treated patients with Class I or III drugs for long-standing persistent AF and compared the outcomes of ablation in those who were successfully converted to sinus rhythm months prior to ablation as opposed to those who were not.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…Recovery has also been demonstrated in human atria 3,[23][24][25][26] . On the other hand, a remarkable vulnerability to recurrence during post-cardioversion period has been observed while reverse remodeling is yet incomplete 23 .…”
Section: Introductionmentioning
confidence: 83%
“…Most studies about electrical atrial remodeling in humans have assessed subjects with and without overt cardiovascular disease [23][24][25]27 . Although micro structural atrial changes have been observed in lone AF 29 , gross and ultra-structural anatomic changes due to underlying cardiac disease, such as fibrosis, may persist indefinitely, despite the restoration to sinus rhythm and may be responsible for persistent electrophysiological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation